Analisis Tingkat Kepercayaan dan Kepuasan Orang Tua dalam Keputusan Menyekolahkan Anak dan Kondisi Prestasi Peserta Didik SDN 165/I Kabupaten Batang Hari - Niki Kosasih; Akhmadi Akhmadi; Azwar Anas; Ade Jermawinsyah Zebua (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The problem of this research is the analysis of the level of trust and satisfaction of parents in the decision to send their children to school and the condition of student achievement at SDN 165/I Batang Hari Regency. The purpose of this study was to analyze the level of trust and satisfaction of parents in the decision to send their children to school and the condition of student achievement at SD N 165/I Batang Hari Regency. The analytical method used is descriptive quantitative using a Likert Scale measuring instrument. The object of the research is the parents of students of SD N 165/I Batang Hari Regency, the number of samples taken is 30 parents of students of SD N 165/I Batang Hari Regency. The analysis tool uses validity and reliability tests. The results showed that the variables used were the level of trust, level of satisfaction, parental decisions and learning achievement. From the results of the respondents' responses, the confidence level of 3.79 was declared good, the satisfaction level of 3.86 was declared satisfied, the parents' decision was 3.96 was declared good, and learning achievement was 4.17 was declared good.